THE DIFFICULTIES OF LEARNING AND HIS CAUSES (Fiep Bulletin - online, 2016)
The question of the difficulties of learning debated all over the world. In Brazil and Latin America has won worrisome proportions. Prepare the student to learn to learn. Prepare the student to learn to learn. The attention of the students with difficulty of learning (DAS) can be described like generalized, affecting the learnings (school and no school), and like bass, affecting varied and important appearances of the development of the person, through the proposal that the educators confront the situation through training continued, ensuring education of quality. The aim of east is conscience the professor of his knowledge through his professional qualification, of his attitudes and expectations about the difficulties of learning (Of the) and of the future of the student. It proposes to the educator the analysis of the context, immediate environmental conditions in that it occurs the processor education-learning (number of students, specific circumstances in that it presents the task, etc.). In addition, conditions mediates (linguistic referents, cultural, etc. of the social and cultural group of origin of the student), with the evaluation psychic pedagogical. The professor thinking his paper of educator will realize changes in the pedagogical practice adapting the peculiarities of the student using instruments differentiated of evaluation, or teach to think by means of the flexible curriculum. Task of the professor in the class integrated splitting of this approach and evaluating particularly the characteristics of the students with difficulties of learning, with difficulties and organizing his knowledge's,  activating his diagrams, for communicating with his mates, and consistently, sharing meanings and attributing a sense to his learning. Considering characteristic that ensure results more positive such relations: conjoint Activities carefully planned, opportunities for the cooperation, surveillance and the knowledge of the didactic of the matter taught and ease to simplify learning.
Keywords: Learning; Difficulties; psychic pedagogical.